Sophora moocroftiana seeds ethanol extract regulates NLRP3 inflammasome activation and pyroptosis via ROS/TXNIP pathway to amelioration of NAFLD in vitro and in vivo - Yuan, Ruiying; Gui, Mingan; Huang, Shan; Ciren, Yangzhen; Zhuoma, Dongzhi; Yang, Guibin; Zhang, Wendong; Wang, Sicen; Li, Bin (Frontiers in Pharmacology, 2025)
BackgroundSophora moorcroftiana (Benth.) Baker is a perennial shrub endemic to the Tibetan Plateau. Its seeds are traditional Tibetan medicine for treating jaundice, hepatitis, purulent tonsillitis, diphtheria, and parasitosis.Aim of the studyThe aim of this research is to explore the possible processes by which the 70% ethanol extract of S. moocroftiana seeds (SMS) imparts healing effects in NAFLD what is done by simulating the disease state of NAFLD via the creation of a lipid accumulation model in HepG2 cells induced by FFA, and a NAFLD model in C57BL/6J mice induced by HFD.Materials and methodsThe experiment used HFD fed C57BL/6J mice to establish a NAFLD model, which was divided into a control group, HFD model group, different doses of SMS groups, and a Silymarin group. Were used in the experiment. SMS could improve lipid accumulation, reduce oxidative stress and inflammatory response, which confirmed the improvement effect of SMS on NAFLD. The protective mechanism of SMS on HepG2 cell lipid accumulation model was further verified by qRT-PCR, WB, ELISA, and other methods.ResultsIn vitro and in vivo experiments showed that SMS could inhibit ROS and TXNIP dissociation, regulate NLRP3/caspase 1/GSDMD pathway to inhibit pyroptosis, and reduce the release of inflammatory factors such as TNF-α, IL-6, IL-18, and IL-1β, thereby improving the symptoms of lipid accumulation and oxidative stress. These results suggest that SMS can improve NAFLD via regulating pyroptosis.ConclusionSMS has promising therapeutic potential in NAFLD management by inhibiting the activation of the NLRP3 inflammasome and pyroptosis via ROS/TXNIP pathway in hepatocytes.